Pengaruh Kompensasi, Disiplin Kerja dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan pada Perusahaan PT. Fimaha Serang - Burmana, Bayu; Angga, Dimas (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to examine the effects of compensation, work discipline, and motivation on employee productivity in PT Fimaha Serang. The study utilized a multiple linear regression analysis to investigate the relationships between the independent variables (compensation, work discipline, and motivation) and the dependent variable (employee productivity). Data was collected from 50 employees working in the production department, and a structured questionnaire was used for data collection. The findings indicated that work discipline had a significant and positive impact on employee productivity, while compensation and motivation showed positive effects, but their contributions were weaker and did not reach statistical significance at the 0.05 level. This study highlights the importance of work discipline in enhancing employee productivity and suggests that further investigation is needed to understand the roles of compensation and motivation in improving employee performance. These findings provide valuable insights for PT Fimaha Serang in optimizing factors that can boost employee productivity, particularly by emphasizing the importance of maintaining and improving work discipline. Further analysis and consideration are recommended when formulating compensation and motivation policies to enhance overall employee productivity.